Information Use in Integrity Systems: Testing the potential for Automated Content Analysis of Local Government Documents. (4th March 2022) - McLeod, Sam; Papavassiliou, Leanna; Clydesdale, Reece
Abstract: The transparency of local government decision-making commonly depends on the discovery and use of information by a wide range of participants acting within the surrounding local integrity system. The roles of external organizations (including the media, academics, and non-government institutions) in using information to perform oversight roles is an important characteristic of local integrity systems. However, even in a relative deluge of document-based local government information, pernicious forms of unethical decision-making can evade immediate detection, hidden in plain view within archives of pages which are too expansive to be manually scrutinized. Responding to numerous examples of failed internal governance in local governments in Australia, we profile the experimental development of a prototype system intended to systematically extract information from meeting minutes. We identify how elementary differences in document expression constrains many innovative uses of these records to support the identification of potentially unethical decision-making. Drawing together the integrity systems and information accessibility literature, we conclude that improved integration of information standards in local government documents holds immense potential in expanding how local integrity systems act to foster ethical decision-making among elected local government officials.